TANGGUNG JAWAB PEMILIK INDEKOST TERHADAP KEHILANGAN BARANG PENYEWA INDEKOST BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Prasetya, Lucky; Agus, Dede; Efriyanto, Efriyanto (LPPM Universitas Bina Bangsa, 2025)
This research discusses the legal responsibility of boarding house owners for the loss of tenants' goods based on Law Number 8 of 1999 concerning Consumer Protection. Boarding house rental agreements are often made verbally without clarity on the boarding house owner's responsibility for the loss of the tenant's belongings. Based on an analysis of Articles 1709 and 1710 of the Civil Code and Article 19 of the Consumer Protection Law, boarding house owners are obliged to provide protection for tenants' belongings. The research uses empirical juridical methods by collecting primary and secondary data through field and literature studies. The research results show that loss of goods at boarding houses often occurs due to boarding house owners' negligence in providing adequate security facilities. Legal efforts and consumer protection are the keys to overcoming this problem.